Analysis the Effect of Coconut Production Risk and Price on the Economic Behavior of Coconut Farmers in Seruyan District, Central Borneo Province, Indonesia - Rusdi, Rusdi; Harianto, Harianto; Hartoyo, Sri; Novianti, Tanti (International Journal of Economics and Financial Issues, 2021)
Coconut farmers are always faced with risks, including the risk of production and price risk. This production risk causes the productivity of the head to decline. In addition, the price risk faced by farmers will also have an impact on the income received so that in the end it will affect the farmer household decision making in allocating existing resources. The purpose of this study was to analyze the effect of changes in the level of production risk and price on farmer household behavior in coconut farming production decisions. This research was conducted in Seruyan District, Central Borneo Province with 200 farmers as respondents. The results showed that there was a risk that production would increase the use of herbicides, reduce the allocation of time to use male labor in the family on family farms and increase the use of male labor from outside the family and reduce spending on health, education and household savings. Meanwhile, the price risk will result in reduced use of female labor from outside the family, reduced non-food, education expenditure and reduced business investment. Keywords: Coconut farmer household economic behavior, production risk, price risk. JEL Classifications: D10, D13, D14, Q12 DOI: https://doi.org/10.32479/ijefi.11340